2011
DOI: 10.1016/j.clim.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the humoral autoreactivity to zinc transporter 8 between childhood- and adult-onset type 1 diabetes in Japanese patients

Abstract: The aim of this study was to evaluate the humoral autoreactivity to zinc transporter 8 (ZnT8) depending on the clinical phenotype of type 1 diabetes (T1D). ZnT8 autoantibodies (ZnT8A) were determined by radioimmunoassay using carboxy-terminal ZnT8 constructs in 57 childhood-onset (CO), 97 adult-onset (AO), and 85 fulminant T1D. The ZnT8A frequency was higher in CO patients and decreased with increasing age of onset from 70% to 24% (P trend <0.005). None of patients with fulminant T1D were positive for ZnT8A. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…ZnT8A were also determined by radioligand binding assay (RBA) using human ZnT8 cDNA as described previously [7]. The human ZnT8 cDNA construct used in this assay was a fusion of the cytoplasmic carboxy-terminal domains (amino acids 268-369) of ZnT8 carrying either 325Trp or 325Arg with a linker peptide.…”
Section: Znt8 Autoantibody Radioligand Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…ZnT8A were also determined by radioligand binding assay (RBA) using human ZnT8 cDNA as described previously [7]. The human ZnT8 cDNA construct used in this assay was a fusion of the cytoplasmic carboxy-terminal domains (amino acids 268-369) of ZnT8 carrying either 325Trp or 325Arg with a linker peptide.…”
Section: Znt8 Autoantibody Radioligand Binding Assaymentioning
confidence: 99%
“…TSH receptor autoantibodies were measured using an RIA kit provided by Yamasa Corporation (Chiba, Japan). IA-2A were determined by RBA as previously described [7].…”
Section: Detection Of Other Autoantibodiesmentioning
confidence: 99%
“…Previous studies have reported that autoantibodies to ZnT8 (ZnT8A) are detected in 60-80 % of Caucasian patients with type 1 diabetes. With radioligand binding assay using in vitro transcribed/translated 35 S-labeled ZnT8 protein, we identified ZnT8A in 58% patients with acute-onset and in 20% with slow-onset type 1 diabetes in the Japanese population [28]. Furthermore, the prevalence of ZnT8A was inversely related to the onset age with the highest prevalence of 70% in patients aged < 10 years (Fig.…”
Section: Zinc Transportersmentioning
confidence: 85%
“…With the combination analysis using four biochemically characterized anti-islet autoantibodies, 94% of Japanese patients with type 1 diabetes are classified as type 1A diabetes [28] (Table 1). However, the clinical utility of ZnT8A is limited over testing GADA, IA-2A, and IAA; i.e.…”
Section: Znt8 Autoantibodies As a Diagnostic Tool For Type 1a Diabetesmentioning
confidence: 99%
“…Zinc is crucial for proper storage, secretion and function of insulin and ZnT8 is specifically expressed in pancreatic β cells. The proportion of T1D patients positive for ZnT8 autoantibodies ranges between 24%-80%, depending on the study (Kawasaki et al, 2011;Wenzlau et al, 2007).…”
Section: Other Autoantigensmentioning
confidence: 99%